Influence of Sharia Financial Literacy,Financial Attitudes And Perceptionson Interest In Using Sharia Banking - Anne Haerany; Sri Aneza (PT. Anagata Sembagi Education, 2024)
Sharia banking has been established in Indonesia for approximately 33 years, but its market share is still very small, namely around 7.21% of total commercial bank assets. This study aims to explain the effect of Islamic Financial Literacy, Attitudes and Perceptions of Finance on Interest in Using Islamic Banking Services with Religiosity as a Moderating Variable in Sharia Economics Students in Region 3 Cirebon. Quantitative research with purposive sampling data collection with 100 respondents. The data obtained was analyzed using SEM-PLS version 3.0 software. The results showed that Sharia Financial Literacy and Financial Attitudes did not have a significant effect on interest in using Islamic banking services, this was due to several factors including the lack of maximum Islamic financial literacy carried out so that it has not fostered understanding among students, as well as the financial attitudes of students, especially in region 3 Cirebon, have not reached the stage of making the right decisions in planning and managing their finances. While perceptions have a significant effect on interest in using Islamic banking services, this is influenced by information obtained from unpleasant past experiences related to conventional finance, news that develops about Islamic finance and the values adopted in the environment where they study. Religiosity cannot moderate Islamic Financial Literacy, Financial Attitudes, and Perceptions of Interest in Using Islamic Banking Services, this is because the value of religiosity used as a benchmark by students is still focused on matters of worship, but has not expanded to matters of muamalah.